Strategi Viral Marketing dan Brand Love dalam Mendorong Repurchase Intention pada Konsumen Buttonscarves di Kota Medan: Penelitian - Nabila Fahriani Pane; Onan Marakali Siregar (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Muslim fashion industry in Indonesia is becoming increasingly competitive, encouraging brands to enhance brand awareness and maintain customer loyalty. Buttonscarves, as one of the Muslim fashion brands, utilizes viral marketing and brand love to attract its consumers. However, the strategies that have been implemented are not entirely effective, as many consumers only purchase when viral trends occur, and the intense competition makes it easier for them to switch to other brands. This study aims to analyze the influence of viral marketing and brand love on repurchase intention among Buttonscarves consumers in Medan City. This research uses a quantitative approach with an associative research type. The sampling technique used is purposive sampling with a total of 100 respondents. Primary data were obtained through the distribution of questionnaires to Buttonscarves consumers, while secondary data were gathered through literature studies. The data analysis techniques include validity test, reliability test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results show that viral marketing has a positive and significant effect on repurchase intention, with a coefficient value of 0.373 and a significance level of 0.000. This indicates that interactive social media marketing campaigns can encourage consumers to purchase products. Furthermore, brand love has a more dominant effect on repurchase intention, with a coefficient of 0.402 and a significance value of 0.000. The coefficient of determination (R) value of 0.842 indicates a strong relationship between viral marketing and brand love toward repurchase intention.